m-Aminophenylboronate agarose specifically binds capped snRNA and mRNA. - Wilk, H E (1982)
m-Aminophenylboronate-substituted agarose binds specifically RNA chains carrying a mature 5' cap. The binding occurs most effectively at pH greater than 8 and involves diester formation between the negatively charged tetrahedric boronate group and the cisdiol of the ribose of the cap. The positive charge introduced by the m7G methylation is necessary for efficient binding although two closely spaced cis-diol groups alone (as in the cap analog NADH) are sufficient for binding. Non-capped RNA (like poly (U) and rRNA) or decapped RNA are not bound. It is shown that the matrix can be used for the isolation of capped small nuclear RNA and mRNA.